CORPORATE BRANDING COWORKING PLACE IN BANDUNG (CORPORATE BRANDING COWORKING SPACE DI BANDUNG) - Damayanti, Dewi; Novianti, Evi; Priyatna, Centurion C. (Prodi Teknologi Pendidikan, 2017)
The title of this research is â€œCorporate Branding Coworking Space in Bandungâ€ with the subtitle is â€œDescriptive Study of Corporate Branding Coworking Space in Bandung to Create Product Differentiationâ€. The high demand for economical workspace makes business coworking space growing. The growth happen in Bandung and make the level of competition coworking space in Bandung is quite high, especially with the uniformity of the product offered each coworking space. Seeing these growth, researchers interested in conducting research on how corporate branding coworking space in Bandung to create product differentiation.The purpose of this study is to discover how company create the vision, implemented vision to their corporate culture, and the compability between their vision and image of Bandung Digital Valley, Freenovation, and Ruang Reka that stakeholder created. The method used in this research is descriptive method with qualitative data and Hatch Schultzâ€™s concept of corporate branding. The data collection techniques used in interviews, observation, and documentation study.The result of this study indicate that Bandung Digital Valley, Freenovation, and Ruang Reka focus to introduce the company to their target market. Started from create the vision of the company by founder based on their experiences and business opportunity. Then, the application of corporate vision to corporate culture. Non of Bandung Digital Valley, Freenovation, or Ruang Reka implement the vision into corporate culture. Last, Bandung Digital Valley, Freenovation, and Ruang Reka think it is not a right time to create corporate image because they need to improve the quality of their facility first.Â Â Keywords : corporate branding, product differentiation, Bandung Digital Valley, Freenovation, Ruang RekaJudul penelitian yang diangkat adalah â€œCorporate Branding Coworking Space di Bandungâ€ dengan sub judul Studi Deskriptif mengenai Corporate Branding Coworking Space di Bandung dalam Melakukan Diferensiasi Produkâ€.Â Tingginya kebutuhan akan ruang kerja yang ekonomis membuat bisnis coworking space semakin berkembang. Perkembangan ini terjadi di Bandung dan membuat tingkat persaingan coworking space di Bandung cukup tinggi, terlebih dengan keseragaman produk yang ditawarkan tiap coworking space. Melihat perkembangan tersebut, peneliti tertarik untuk melakukan penelitian mengenai bagaimana corporate branding coworking space di Bandung dalam melakukan diferensiasi produk. Tujuan penelitian ini adalah untuk mengetahui bagaimana pembentukan visi perusahaan, pengimplementasian visi ke dalam budaya, dan kesesuaian citra dengan visi Bandung Digital Valley, Freenovation, dan Ruang Reka yang dihasilkan oleh stakeholder. Mengacu kepada konsep Corporate Branding dari Hatch dan Schultz. Metode penelitian yaitu metode deskriptif dengan data kualitatif. Teknik pengumpulan data dengan wawancara, observasi, dan studi dokumentasi. Setelah melakukan penelitian hasil yang didapat menunjukkan bahwa Corporate branding Bandung Digital Valley, Freenovation, dan Ruang Reka diakui fokus pada pengenalan perusahaan ke target pasarnya. Dimulai dengan pembentukan visi oleh pendiri melihat dari pengalaman dan peluang yang dimiliki. Lalu, penerapan visi pada setiap aspek perusahaan, salah satunya budaya perusahaan tidak dilakukan oleh seluruh coworking space. Terakhir, pembentukan citra kepada stakeholder dirasa belum saatnya karena masih perlu meningkatkan kualitas internal namun sudah ada usaha kesana yang tidak disadari olehÂ Bandung Digital Valley, Freenovation, dan Ruang Reka.Kata Kunci : pembentukan merek perusahaan, diferensiasi produk, Bandung Digital Valley, Freenovation, Ruang Reka.